The Contribution of Neutrophils and NETs to the Development of Type 1 Diabetes - Petrelli, Alessandra; Popp, Sarah K.; Fukuda, Riho; Parish, Christopher R.; Bosi, Emanuele; Simeonovic, Charmaine J. (Frontiers in Immunology, 2022)
Type 1 diabetes (T1D) is an autoimmune disease resulting from the destruction of insulin-producing beta cells in pancreatic islets. T lymphocytes are the claimed pathogenic effectors but abnormalities of other immune cell types, including neutrophils, also characterize T1D development. During human T1D natural history, neutrophils are reduced in the circulation, while accumulate in the pancreas where release of neutrophil extracellular traps (NETs), or NETosis, is manifest. Recent-onset T1D patients also demonstrate activated circulating neutrophils, associated with a unique neutrophil gene signature. Neutrophils can bind to platelets, leading to the formation of platelet-neutrophil aggregates (PNAs). PNAs increase in the circulation during the development of human T1D and provide a mechanism for neutrophil activation and mobilization/recruitment to the pancreas. In non-obese diabetic or NOD mice, T1D autoimmunity is accompanied by dynamic changes in neutrophil numbers, activation state, PNAs and/or NETosis/NET proteins in the circulation, pancreas and/or islets. Such properties differ between stages of T1D disease and underpin potentially indirect and direct impacts of the innate immune system in T1D pathogenesis. Supporting the potential for a pathogenic role in T1D, NETs and extracellular histones can directly damage isolated islets in vitro, a toxicity that can be prevented by small polyanions. In human T1D, NET-related damage can target the whole pancreas, including both the endocrine and exocrine components, and contribute to beta cell destruction, providing evidence for a neutrophil-associated T1D endotype. Future intervention in T1D could therefore benefit from combined strategies targeting T cells and accessory destructive elements of activated neutrophils.